A document-based software traceability to support change impact analysis of object-oriented software - Ibrahim, Suhaimi (2006)
The need for software modifications especially during the maintenance phase, is inevitable and remains the most costly. A major problem to software maintainers is that seemingly small changes can ripple through the entire system to cause major unintended impacts. As a result, prior to performing the actual change, maintainers need mechanisms in order to understand and estimate how a change will affect the rest of the system. Current approaches to software evolution focus primarily on the limited scope of change impact analysis e.g. code. This research is based on the premise that a more effective solution to manage system evolution can be achieved by considering a traceability approach to pre-determine the potential effects of change. The aim of this research is to establish a software traceability model that can support change impact analysis. It identifies the potential effect to software components in the system that does not lie solely on code but extends to other high level components such as design and requirements. As such, in this research, modification to software is therefore considered as being driven by both high level and low level software components. This research applies a comprehensive static and dynamic analysis to provide better impact infrastructures. The main research contribution in this thesis can be seen in the ability to provide a new software traceability approach that supports both top-down and bottom-up tracing. In further proving the concept, some software prototype tools were developed to automate and support the potential effects. The significant achievement of the model was then demonstrated using a case study on a non-trivial industrial application software, and evaluated via a controlled experiment. The results when compared against existing benchmark proved to be significant and revealed some remarkable achievements in its objective to determine change impacts